Study of Sociological Law on Conflict Resolution Through Adat in Aceh Community According to Islamic Law - M. Kasim, Fajri; Nurdin, Abidin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
This study discusses conflict resolution through adat in Acehnese society according to Islamic law. Conflict resolution like this is a solution in the midst of the piling up of cases in the judiciary in Indonesia. This study uses the sociology of law theory which sees that law is a tool to control communities who can resolve conflicts, namely adat and cultural values. The data collection techniques used are; interviews and literature review. The results of this study indicate that conflict resolution with adat mechanisms in the perspective of sociology of law sees law as a tool and means to control and develop society. Law is seen as a means of community development in a better direction. In fact, the judiciary formally advocates for peace by deliberation known as mediation, this is done in the midst of piling up cases that must be resolved by law enforcers. Therefore, adat-based conflict resolution has advantages, among others, maintaining brotherhood and eliminating grudges, fast, cheap, promoting a sense of justice and elasticity. This advantage is possible because of the involvement of adat institutions as social elites that have both social and juridical legitimacy. Conflict resolution through adat is in line with the values of Islamic law, especially in the concept of al-urf, namely adat that do not conflict with sharia. The strong relationship between adat and Islam in Aceh has resulted in this pattern of conflict resolution being viable and enduring to this day.